Improvement of Structural and Technological Parameters of the Innovative Type Climate Chamber - Nikonova, Antonina; Ivaney, Aleksandr; Okuneva, Leonora (KnE Life Sciences, 2020)
While studying the influence of the parameters, characterizing heat removal from the working medium of the chamber, on operational characteristics of the experimental installation, the values of the amperage supplied to the thermoelectric module were being varied from 1.4 to 4.2 A, as well as the degree of chamber adiabaticity was being altered by changing the number of extruded polystyrene foam plates 20 mm thick in the build-up chamber cover from one to 3. The dynamics of the working medium temperature change depending on the amperage supplied to the thermoelectric module is illustrated by graph dependencies. As a result of data processing by constructing the second order orthogonal central composition plan the adequate regression equation was received for the cooling process and the thermo stating of the climate chamber working medium and the conclusion on a rational number of the chamber cover plates (which equals 3) was made. It was found out that upon increasing the amperage supplied to the thermoelectric module and using a three-plate cover the experimental chamber working medium temperature is varied from –2ºC to 11ºC, this can be applied for cooling and thermo stating various objects including biological raw materials of both animal and plant origin as well as non-food objects.